Composite copper powder, preparation method of composite copper powder, semiconductor packaging piece and preparation method of semiconductor packaging piece
By embedding nanocopper into the concave points of microcopper, composite copper powder is prepared, and the electromigration and high cost of nanosilver materials under high temperature and high pressure conditions is solved, efficient sintering activity and low shrinkage effect are achieved, and the reliability of semiconductor packaging is improved.
Patent Information
- Application Number
- CN202510390806.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-31
AI Technical Summary
The existing nanosilver materials have electromigration under high temperature and high pressure conditions and are costly. The nano-copper oxidation and sintering shrinkage are large, making it difficult to meet the high heat dissipation and high reliability requirements of semiconductor devices under high temperature and high pressure conditions.
Using a method of preparing composite copper powder, the advantages of nanocopper and microcopper are combined with the advantages of nanocopper and microcopper, providing sintering active sites and inhibiting sintering shrinkage.
High activity and low shrinkage during low temperature sintering are achieved, reducing costs and improving the connection strength and reliability of semiconductor packages.
Smart Images

Figure CN119897477A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of semiconductor technology, and in particular to a composite copper powder and a preparation method thereof, a semiconductor package and a preparation method thereof. Background Art
[0002] With the requirements of new energy, electronic information industry and other fields for semiconductor devices to serve under high temperature, high pressure and other conditions, power devices and chips have put forward higher requirements for high heat dissipation and high reliability of packaging materials. Although the commonly used nano-silver materials are widely used in the packaging field, there is electromigration in the nano-silver materials during service, and the high cost of nano-silver materials restricts its development. The resistivity and thermal conductivity of metallic copper are close to those of silver, and the cost is only one-tenth of silver. It is inexpensive and has been widely used in the field of packaging and interconnection. However, problems such as oxidation and large sintering shrinkage of nano-copper are still difficult to tackle. Summary of the invention
[0003] The object of the present invention is to provide a composite copper powder and a preparation method thereof, a semiconductor package and a preparation method thereof, so as to solve the problems in the prior art.
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a composite copper powder, comprising the following steps: Weighing a soluble copper salt and a pore-forming agent, dissolving them in a first alkaline solution, and mixing them evenly to obtain a first solution, wherein the molar ratio of copper ions in the soluble copper salt to the pore-forming agent is (12-1):6; the pore-forming agent is an ammonium salt; Weighing a reducing agent and a dispersing agent, and dissolving them in a second alkaline solution to obtain a second solution, wherein the molar ratio of the reducing agent to the copper ions in the soluble copper salt is (10-1):1; The first solution and the second solution are quickly mixed under stirring, and reacted at 80-160° C. for 15-120 minutes. After the reaction is completed, the mixture is cooled to room temperature, and solid-liquid separation is performed to obtain copper particles; the copper particles are in a plush state; The copper particles are added to the solvent, mixed evenly, and then the coating agent is added and stirred for 30-60 minutes, the solid-liquid separation is carried out, and the particles are vacuum dried, and then passed through a 80-800 mesh sieve to obtain particles with a diameter of 1-6 μm and a specific surface area of 0.2-8 m 2 / g of plush micron copper; The micron copper and nano copper with a particle size of 10-100 nm are weighed, the mass ratio of the micron copper to the nano copper is (1-81):9, the micron copper and the nano copper are mixed, and the nano copper is embedded in the pits of the micron copper to obtain a composite copper powder.
[0005] In one embodiment, the size of the pit is ≤100 nm, and the particle size of the nano copper is not greater than the size of the pit; The mixing time of the first solution and the second solution is less than 3 min.
[0006] In one embodiment, the step of mixing the micron copper and the nano copper and embedding the nano copper into the pits of the micron copper to obtain the composite copper powder comprises: The micron copper and the nano copper are premixed for 30-60 minutes to obtain a premix, and then ball milling beads with a diameter of 2-10 mm are added, the mass ratio of the ball milling beads to the premix is (3-20):1, and composite copper powder is obtained after ball milling for 4-20 hours.
[0007] In one embodiment, the ball milling beads are ceramic beads; After ball milling, the powder is passed through a 80-800 mesh sieve to obtain a composite copper powder with a particle size of 1-10 μm.
[0008] In one embodiment, the soluble copper salt includes at least one of copper sulfate, copper nitrate, copper chloride, copper acetate, copper citrate and hydrates thereof; The pore-forming agent includes at least one of ammonium chloride, ammonium bromide, ammonium sulfate, ammonium bicarbonate, ammonium carbonate, urea, ethylenediamine, triethanolamine, and triethylamine.
[0009] In one embodiment, the first alkaline solution and the second alkaline solution both include an alkaline substance and a solvent, the alkaline substance includes at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, ethylenediamine, and ammonia water, and the solvent includes at least one of pure water, ethanol, ethylene glycol, glycerol, isopropanol, and polyethylene glycol; The alkaline substance accounts for 5-30% of the first alkaline solution, and the alkaline substance accounts for 2-20% of the second alkaline solution.
[0010] In one embodiment, the mass ratio of the dispersant to the copper particles is (0.001-0.05): 1; The dispersant includes at least one of gelatin, polyvinyl pyrrolidone, gum arabic, benzimidazole, 2-methylimidazole, 2-phenylimidazole, imidazole, and hexadecyltrimethylammonium bromide; The reducing agent includes at least one of sodium hypophosphite, sodium ascorbate, ascorbic acid, hydrazine hydrate, glucose, sodium borohydride and glycerol.
[0011] In one embodiment, the coating agent includes at least one of stearic acid, oleic acid, benzimidazole, 2-methylimidazole, 2-phenylimidazole and imidazole, and the solvent includes at least one of anhydrous ethanol, ethylene glycol, pure water, acetone, ether, glycerol and acetone; the mass ratio of the coating agent to the copper particles is (0.005-0.1):1.
[0012] The present invention also provides a composite copper powder, which is prepared by the above-mentioned preparation method.
[0013] The present invention also provides a method for preparing a semiconductor package, comprising the following steps: The composite copper powder prepared by the preparation method is used as a raw material to prepare and obtain solder paste; The two substrates are welded with the solder paste to obtain a semiconductor package.
[0014] The present invention also provides a semiconductor package, comprising two substrates and a solder paste layer located between the two substrates, wherein the solder paste layer is prepared using the composite copper powder prepared by the above preparation method as a raw material.
[0015] It can be seen from the above technical solution that the advantages and positive effects of the present invention are: The preparation method of the present invention first prepares a plush micron copper, then forms concave points on the periphery of the plush micron copper, and then disperses and attaches nano copper to the concave points of the micron copper to obtain a composite copper powder. The composite copper powder combines the advantages of nano copper and micron copper, that is, nano copper provides sintering active sites, ensuring that the composite copper powder has high activity during low-temperature sintering, and micron copper inhibits sintering shrinkage. The micron copper is plush and provides a high specific surface area, and the nano copper is attached to the concave points formed by the micron copper during ball milling, so that the composite copper powder is compactly stacked. The cost is reduced by mixing nano copper and micron copper. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic flow diagram of the method for preparing the composite copper powder of the present invention.
[0017] Figure 2 It is a schematic diagram of the principle of embedding nano-copper into the pits of micro-copper in the present invention.
[0018] Figure 3 This is a scanning electron microscope image of Example 2 of the present invention.
[0019] Figure 4 It is a schematic diagram of the sintering of the solder paste prepared by the composite copper powder of Example 2 of the present invention.
[0020] Figure 5 This is a schematic diagram of the sintering of the solder paste prepared from the composite copper powder of Comparative Example 1.
[0021] Figure 6 This is a schematic diagram of the sintering of the solder paste prepared from the copper powder of Comparative Example 2. DETAILED DESCRIPTION
[0022] Typical embodiments that embody the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various changes in different embodiments without departing from the scope of the present invention, and the descriptions and illustrations therein are essentially used for illustration purposes rather than for limiting the present invention.
[0023] In order to further illustrate the principle and structure of the present invention, preferred embodiments of the present invention are now described in detail with reference to the accompanying drawings.
[0024] It should be noted that copper paste prepared from pure nano copper powder is usually used in low temperature interconnection. However, pure nano copper powder has poor oxidation resistance, large sintering shrinkage leading to cracks, and the cost of nano copper powder is high.
[0025] Therefore, the present invention provides a method for preparing a composite copper powder, which can prepare a composite copper powder with low cost and suitable for low-temperature sintering.
[0026] The preparation method of the composite copper powder comprises the following steps: first preparing a fuzzy micron copper, then forming concave points on the periphery of the fuzzy micron copper, and then dispersing and attaching nano copper to the concave points of the micron copper to obtain the composite copper powder. The composite copper powder combines the advantages of nano copper and micron copper, that is, nano copper provides sintering active sites, ensuring that the composite copper powder has high activity during low-temperature sintering, and micron copper inhibits sintering shrinkage. The micron copper is fuzzy and provides a high specific surface area, and the nano copper is attached to the concave points formed by the micron copper during ball milling, so that the composite copper powder is compactly stacked. The cost is reduced by mixing nano copper and micron copper.
[0027] The preparation method of the composite copper powder is specifically introduced below.
[0028] See also Figure 1 The preparation method of the composite copper powder comprises the following steps: S100, weighing a soluble copper salt and a pore-forming agent, dissolving them in a first alkaline solution, and mixing them evenly to obtain a first solution. The molar ratio of copper ions in the soluble copper salt to the pore-forming agent is (12-1):6. The pore-forming agent is an ammonium salt.
[0029] Specifically, the soluble copper salt includes at least one of copper sulfate, copper nitrate, copper chloride, copper acetate, copper citrate and hydrates thereof. The solubility here includes both easily soluble and slightly soluble.
[0030] The soluble copper salt may be any one of the above mentioned salts, or a mixture of two, three or more thereof.
[0031] The pore-forming agent is an ammonium salt. Specifically, the pore-forming agent includes at least one of ammonium chloride, ammonium bromide, ammonium sulfate, ammonium bicarbonate, ammonium carbonate, urea, ethylenediamine, triethanolamine, and triethylamine. That is, the pore-forming agent can be any one of the above, or a mixture of two, three, or more.
[0032] The pore former is used to generate gas evolution during the process of copper ions being reduced to copper, thereby forming pores around the copper.
[0033] Specifically, the molar ratio of copper ions in the soluble copper salt to the pore-forming agent is (12-1): 6. With this ratio, pores can be formed on the surface of the copper particles.
[0034] The first alkaline solution includes an alkaline substance and a solvent. The alkaline substance includes at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, ethylenediamine, and ammonia water. The alkaline substance can be any one of the above, or any two or more.
[0035] The solvent includes at least one of pure water, ethanol, ethylene glycol, glycerol, isopropanol and polyethylene glycol. The solvent can be any one of the above, or any two or more.
[0036] In the first alkaline solution, the mass proportion of the alkaline substance is 5-30%, wherein the mass proportion here refers to the percentage of the mass of the alkaline substance to the total mass of the first alkaline solution.
[0037] Exemplarily, the first alkaline solution includes sodium hydroxide and pure water, and the mass proportion of sodium hydroxide is 5%. Alternatively, the first alkaline solution includes sodium hydroxide, potassium hydroxide and pure water, and the sum of the mass of sodium hydroxide and potassium hydroxide accounts for 5%.
[0038] S200, weighing a reducing agent and a dispersing agent, and dissolving them in a second alkaline solution to obtain a second solution, wherein the molar ratio of the reducing agent to the copper ions in the soluble copper salt is (10-1):1.
[0039] The mass ratio of the dispersant to the copper particles is (0.001-0.05): 1. The copper particles are theoretically prepared products from the reaction of soluble copper salts and reducing agents.
[0040] The reducing agent includes at least one of sodium hypophosphite, sodium ascorbate, ascorbic acid, hydrazine hydrate, glucose, sodium borohydride and glycerol. The reducing agent can be any one of the above, or any two or more.
[0041] The dispersant includes at least one of gelatin, polyvinyl pyrrolidone, gum arabic, benzimidazole, 2-methylimidazole, 2-phenylimidazole, imidazole, and hexadecyltrimethylammonium bromide. The dispersant can be any one of the above, or any two or more.
[0042] The second alkaline solution includes an alkaline substance and a solvent. The alkaline substance includes at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, ethylenediamine, and ammonia water. The solvent includes at least one of pure water, ethanol, ethylene glycol, glycerol, isopropanol, and polyethylene glycol. In the second alkaline solution, the mass proportion of the alkaline substance is 2-20%. The second alkaline solution can refer to the description of the first alkaline solution.
[0043] In the above two steps, the soluble copper salt and the reducing agent are respectively prepared as the first solution and the second solution, which can avoid the reaction between the two during the mixing process. At the same time, the soluble copper salt and the pore-forming agent are dispersed in the first alkaline solution, which is conducive to the pore-forming agent and the soluble copper salt to form a complex first and disperse evenly. Mixing the reducing agent with the second alkaline solution in advance is conducive to the activation of the reducing agent.
[0044] S300, the first solution and the second solution are mixed rapidly under stirring, and reacted at 80-160°C for 15-120 minutes. After the reaction is completed, the mixture is cooled to room temperature, and the solid and liquid are separated to obtain copper particles. The copper particles are in a plush state.
[0045] Specifically, the mixing time of the first solution and the second solution is less than 3 min. The specific time varies depending on the volume. For example, during the experiment, the first solution can be directly poured into the second solution while stirring.
[0046] The first solution and the second solution undergo a reduction reaction at 80-160° C., that is, the copper ions are reduced to copper element.
[0047] In an alkaline environment, copper ions undergo an oxidation-reduction reaction with a reducing agent, and the copper ions are reduced to copper. In the process of copper ions being reduced to copper, copper nuclei are formed and aggregated, and the pore-forming agent ammonium salt reacts with hydroxide ions in an alkaline environment to produce ammonia gas and overflow. Ammonia gas is corrosive, so when ammonia gas overflows from the surface of copper particles, fuzzy holes are generated on the surface of copper particles. Therefore, the periphery of the copper particles finally formed after the reaction is completed has multiple fuzzy holes.
[0048] In the above reaction process, the pore-forming agent ammonium salt can also form a complex with copper ions, and the complex gradually dissociates during the reduction reaction of copper ions. After the ammonium salt combines with copper ions, hydroxide ions are dissociated, which increases the alkalinity of the solution, increases the reaction rate of oxidation-reduction, and increases the growth rate of copper crystal nuclei.
[0049] Therefore, the preparation method of the present application adjusts the redox reaction rate by controlling the alkaline concentration of the first alkaline solution and the second alkaline solution, uses ammonium salt as a pore-forming agent and controls the molar ratio of the pore-forming agent to copper to control the morphology and porosity of the prepared copper, and controls the size of the prepared copper by selecting the above-mentioned reducing agent and controlling the dosage. By selecting the type of ammonium salt and controlling the concentration of the alkali solution, the reaction rate is increased, the copper microcrystals maintain a high growth rate, and plush holes are formed during the overflow of the strong alkaline gas.
[0050] The purpose of adding the dispersant is to inhibit the agglomeration of the formed copper particles due to the fast reaction rate and to improve the dispersibility.
[0051] In this embodiment, the solid-liquid separation adopts the method of centrifugal washing. In other embodiments, other methods such as filtration can also be adopted. The specific method can be selected according to actual needs.
[0052] S400, add copper particles to the solvent, mix well, add coating agent, stir for 30-60 minutes, separate solid and liquid, and vacuum dry to obtain micron copper, and then pass through a 80-800 mesh sieve to obtain a particle size of 1-6μm and a specific surface area of 0.2-8m 2 / g of plush micron copper.
[0053] The coating agent includes at least one of stearic acid, oleic acid, benzimidazole, 2-methylimidazole, 2-phenylimidazole and imidazole. The solvent includes at least one of anhydrous ethanol, ethylene glycol, pure water, acetone, ether, glycerol and acetone.
[0054] The mass ratio of the coating agent to the copper particles is (0.005-0.1): 1. That is, the coating agent and the copper particles are mixed in the above ratio.
[0055] The copper particles are subjected to an anti-oxidation treatment by using a coating agent to prevent the surface of the copper particles from being oxidized to form copper oxide.
[0056] Since the outer periphery of the copper particle has pits, the outer periphery of the micron copper also has a plurality of pits.
[0057] S500, weighing micron copper and nano copper with a particle size of 10-100 nm, the mass ratio of micron copper to nano copper is (1-81):9. Mixing the micron copper and nano copper and embedding the nano copper into the concave points of the micron copper to obtain composite copper powder.
[0058] The size of the pit is ≤100 nm, and the particle size of the nano copper is not larger than the size of the pit, so that the nano copper can be embedded in the pit.
[0059] Specifically, the steps of mixing micron copper and nano copper and embedding the nano copper into the pits of the micron copper to obtain the composite copper powder include: The micron copper and nano copper are premixed for 30-60 minutes to obtain a premix, and then ball milling beads with a diameter of 2-10 mm are added. The mass ratio of the ball milling beads to the premix is (3-20):1. After ball milling for 4-20 hours, composite copper powder is obtained.
[0060] The role of premixing is to make the nano-copper fully contact with the micro-copper so that the nano-copper can enter the pits during subsequent ball milling.
[0061] The ball milling beads are ceramic beads, and are specifically made of zirconium oxide or aluminum oxide.
[0062] Ball milling is performed in a ball mill. During the ball milling process, the rotation speed can also be adjusted. For example, the rotation speed is 200r / min. The specific rotation speed can be set according to actual needs.
[0063] Furthermore, after ball milling, the composite copper powder is passed through a sieve of 80-800 mesh to obtain a composite copper powder with a particle size of 1-10 μm. The composite copper powder within this particle size range has a higher specific surface area than the ball copper of the same size, making the sintering activity higher. The composite copper powder within this specific surface area range is larger in size than the ball copper of the same surface area, thereby being able to inhibit shrinkage cracking during drying and sintering.
[0064] That is, the ball milling beads and the composite copper powder are separated by the action of the sieve.
[0065] During the ball milling process, the ceramic balls and copper powder are in repeated contact, and the contact part is highly active. During the ball milling process, the nanospheres are mixed with the plush microspheres, and some of the nanospheres enter the plush holes on the surface of the microspheres, or are half-embedded in the plush fibers. Through ball milling micro-flaking, the nanosphere copper can be further smashed into the concave points of the surface plush fibers, such as Figure 2 shown.
[0066] The plush micron copper powder is first micro-flaked, and the plush holes on the surface form pits. The nano copper powder is smashed into the pits, making the nano copper powder and micro copper powder combine more tightly. The nano copper adheres to the pits on the surface of the micro-flaked plush copper to form a composite copper powder.
[0067] In this embodiment, the mechanical grinding is used to achieve the embedding of nano copper into the pits of micro copper by physical means. In other embodiments, the nano copper can also be combined into the pits of micro copper by chemical means.
[0068] In summary, the preparation method of the present application has the following advantages: 1. The composite copper powder in this application disperses and connects the nanopowder in the concave points of micron copper, and the nano-copper is used to provide sintering activity points, thereby ensuring the high sintering activity of the composite copper powder. The micron copper is used to inhibit sintering shrinkage, thereby solving the problem of drying and sintering cracking.
[0069] 2. The micron copper prepared in the present application has a plush morphology. Under the same scale, the plush copper powder has a higher sintering activity. The preparation method of the plush copper powder is simple, the equipment is simple, and it is conducive to mass production.
[0070] 3. The mixture of micron copper and nano copper reduces the proportion of nano copper and reduces the cost, thus achieving higher economic benefits.
[0071] 4. This application uses a physical method to embed nano-copper into the pits of micron-copper without introducing a large amount of organic solvents, which is relatively environmentally friendly and convenient for mass production.
[0072] The present application also provides a composite copper powder, which is prepared by the above-mentioned preparation method.
[0073] The present application also provides a method for preparing a semiconductor package, comprising the following steps: S600, preparing and obtaining solder paste using the copper powder prepared by the above preparation method as raw material.
[0074] Specifically, the solid content of the solder paste is 60%-90%.
[0075] S700, soldering two substrates with solder paste to obtain a semiconductor package.
[0076] Specifically, the steps of welding two substrates to obtain a semiconductor package include: S710, forming a solder paste layer on one of the substrates using solder paste.
[0077] S720, placing another substrate on the solder paste layer to obtain an intermediate component.
[0078] S730. Under a protective gas atmosphere, the intermediate piece is subjected to heat and pressure treatment to obtain a semiconductor package, wherein the heat preservation temperature is between 180° C. and 320° C., the pressure is between 1 MPa and 20 MPa, and the heat and pressure treatment time is between 1 min and 60 min.
[0079] Protective gas atmosphere such as helium, nitrogen, etc.
[0080] The present application also provides a semiconductor package, comprising two substrates and a solder paste layer located between the two substrates. The solder paste layer is prepared using the composite copper powder prepared by the above preparation method as a raw material.
[0081] The inventors of the present application have achieved the preparation of the composite copper powder by strictly designing the content of each component and the parameters in each step. The preparation method of the composite copper powder is introduced below through various embodiments.
[0082] Example 1 The preparation method of the composite copper powder in this embodiment comprises the following steps: S11, weighing a soluble copper salt and a pore-forming agent, dissolving them in a first alkaline solution, and mixing them evenly to obtain a first solution. The molar ratio of copper ions in the soluble copper salt to the pore-forming agent is 1:2.
[0083] Specifically, the soluble copper salt is copper acetate monohydrate. The pore-forming agent is ammonium chloride. The first alkaline solution includes sodium hydroxide and pure water, and the mass proportion of sodium hydroxide is 5%.
[0084] S12, weighing a reducing agent and a dispersing agent, and dissolving them in a second alkaline solution to obtain a second solution, wherein the molar ratio of the reducing agent to the copper ions in the soluble copper salt is 10:1.
[0085] The reducing agent is sodium hypophosphite monohydrate. The dispersing agent is gelatin. The mass ratio of the dispersing agent to the copper particles is 0.05:1.
[0086] The second alkaline solution includes sodium hydroxide and pure water, and the mass proportion of sodium hydroxide is 2%.
[0087] S13, the first solution and the second solution are mixed rapidly under stirring, and reacted at 80° C. for 120 min. After the reaction is completed, the mixture is cooled to room temperature, and the solid and liquid are separated to obtain copper particles. The copper particles are in a plush state.
[0088] Specifically, the mixing time of the first solution and the second solution is 30 s.
[0089] S14, adding the copper particles into the solvent, mixing evenly, adding the coating agent, stirring for 50 minutes, separating the solid and the liquid, and vacuum drying to obtain micron copper.
[0090] The coating agent is benzimidazole, the solvent is anhydrous ethanol, and the mass ratio of the coating agent to the copper particles is 0.005:1.
[0091] In this embodiment, the specific surface area of micron copper is 0.21m 2 / g, and the average particle size is 6μm. S15, weighing micron copper and nano copper with a particle size of 10 nm, the mass ratio of micron copper to nano copper being 1:9. Mixing the micron copper and nano copper and embedding the nano copper into the pits of the micron copper to obtain composite copper powder.
[0092] Specifically, micron copper and nano copper were premixed for 30 minutes to obtain a premix, and then zirconium beads with a diameter of 5 mm were added. The mass ratio of the premix to the zirconium beads was 1:20, and the composite copper powder was obtained after ball milling for 4 hours.
[0093] The nanometer powder in the composite copper powder is attached to the micro-flaked plush-like pits.
[0094] Example 2 The preparation method of the composite copper powder in this embodiment comprises the following steps: S21, weighing a soluble copper salt and a pore-forming agent, dissolving them in a first alkaline solution, and mixing them evenly to obtain a first solution. The molar ratio of copper ions in the soluble copper salt to the pore-forming agent is 1:6.
[0095] Specifically, the soluble copper salt is copper acetate monohydrate. The pore-forming agent is ammonium chloride. The first alkaline solution includes sodium hydroxide and pure water, and the mass proportion of sodium hydroxide is 30%.
[0096] S22. Weigh a reducing agent and a dispersing agent, and dissolve them in a second alkaline solution to obtain a second solution, wherein the molar ratio of the reducing agent to the copper ions in the soluble copper salt is 5:1.
[0097] The reducing agent is sodium ascorbate and glycerol. The dispersant is gelatin. The mass ratio of the dispersant to the copper particles is 0.001:1.
[0098] The second alkaline solution includes sodium hydroxide and pure water, wherein the mass proportion of the sodium hydroxide is 10%.
[0099] S23, the first solution and the second solution are mixed rapidly under stirring, and reacted at 80° C. for 60 minutes. After the reaction is completed, the mixture is cooled to room temperature, and the solid and liquid are separated to obtain copper particles. The copper particles are in a plush state.
[0100] Specifically, the mixing time of the first solution and the second solution is 50 s.
[0101] S24, adding the copper particles into the solvent, mixing evenly, adding the coating agent, stirring for 40 minutes, separating the solid and the liquid, and vacuum drying to obtain micron copper.
[0102] The coating agent is oleic acid, the solvent is ethanol, and the mass ratio of the coating agent to the copper particles is 0.005:1.
[0103] In this embodiment, the specific surface area of micron copper is 3.63m 2 / g, and the average particle size is 1.94μm.
[0104] S25, weighing micron copper and nano copper with a particle size of 30 nm, the mass ratio of micron copper to nano copper being 7:3. Mixing the micron copper and nano copper and embedding the nano copper into the pits of the micron copper to obtain composite copper powder.
[0105] Specifically, micron copper and nano copper were premixed for 60 minutes to obtain a premix, and then zirconium beads with a diameter of 10 mm were added, and the mass ratio of zirconium beads to the premix was 5:1. Composite copper powder was obtained after ball milling for 12 hours.
[0106] The nanometer powder in the composite copper powder is attached to the micro-flaked plush-like pits.
[0107] Example 3 The preparation method of the composite copper powder in this embodiment comprises the following steps: S31, weighing a soluble copper salt and a pore-forming agent, dissolving them in a first alkaline solution, and mixing them evenly to obtain a first solution. The molar ratio of copper ions in the soluble copper salt to the pore-forming agent is 1:6.
[0108] Specifically, the soluble copper salt is copper acetate monohydrate. The pore-forming agent is ammonium sulfate. The first alkaline solution includes sodium hydroxide, pure water and anhydrous ethanol, and the mass proportion of sodium hydroxide is 25%.
[0109] S32, weighing a reducing agent and a dispersing agent, and dissolving them in a second alkaline solution to obtain a second solution, wherein the molar ratio of the reducing agent to the copper ions in the soluble copper salt is 5:1.
[0110] The reducing agent is ascorbic acid and glycerol. The dispersant is gum arabic. The mass ratio of the dispersant to the copper particles is 0.05:1.
[0111] The second alkaline solution includes sodium hydroxide, pure water and anhydrous ethanol, and the mass proportion of sodium hydroxide is 20%.
[0112] S33, the first solution and the second solution are mixed rapidly under stirring, and reacted at 160° C. for 60 minutes. After the reaction is completed, the mixture is cooled to room temperature, and the solid and liquid are separated to obtain copper particles. The copper particles are in a plush state.
[0113] Specifically, the mixing time of the first solution and the second solution is 58 s.
[0114] S34, adding the copper particles into the solvent, mixing evenly, adding the coating agent, stirring for 60 minutes, separating the solid and the liquid, and vacuum drying to obtain micron copper.
[0115] The coating agent is methylimidazole, the solvent is anhydrous ethanol, and the ratio of the mass of the coating agent to the mass of the copper particles is 0.01:1.
[0116] In this embodiment, the specific surface area of micron copper is 7.98 m 2 / g, and the average particle size is 1μm.
[0117] S35, weighing micron copper and nano copper with a particle size of 100 nm, the mass ratio of micron copper to nano copper being 9: 1. Mixing the micron copper and nano copper and embedding the nano copper into the pits of the micron copper to obtain composite copper powder.
[0118] Specifically, micron copper and nano copper were premixed for 40 minutes to obtain a premix, and then zirconium beads with a diameter of 2 mm were added, and the mass ratio of zirconium beads to the premix was 10:1. Composite copper powder was obtained after ball milling for 4 hours.
[0119] Example 4 The preparation method of the composite copper powder in this embodiment comprises the following steps: S41, weighing a soluble copper salt and a pore-forming agent, dissolving them in a first alkaline solution, and mixing them evenly to obtain a first solution. The molar ratio of copper ions in the soluble copper salt to the pore-forming agent is 1:4.
[0120] Specifically, the soluble copper salt is copper chloride. The pore-forming agent is ammonium chloride. The first alkaline solution includes sodium hydroxide and pure water, and the mass proportion of sodium hydroxide is 15%.
[0121] S42, weighing a reducing agent and a dispersing agent, and dissolving them in a second alkaline solution to obtain a second solution, wherein the molar ratio of the reducing agent to the copper ions in the soluble copper salt is 5:1.
[0122] The reducing agent is sodium hypophosphite. The dispersing agent is polyvinyl pyrrolidone. The mass ratio of the dispersing agent polyvinyl pyrrolidone to the copper particles is 0.001:1.
[0123] The second alkaline solution includes sodium hydroxide and pure water, and the mass proportion of sodium hydroxide is 5%.
[0124] S43, the first solution and the second solution are mixed rapidly under stirring, and reacted at 90° C. for 120 min. After the reaction is completed, the mixture is cooled to room temperature, and the solid and liquid are separated to obtain copper particles. The copper particles are in a plush state.
[0125] Specifically, the mixing time of the first solution and the second solution is 58 s.
[0126] S44, adding copper particles to the solvent, mixing evenly, adding a coating agent, stirring for 35 minutes, separating the solid and the liquid, and vacuum drying to obtain micron copper.
[0127] The coating agent is stearic acid, the solvent is ethanol, and the mass ratio of the coating agent to the copper particles is 0.01:1.
[0128] In this embodiment, the specific surface area of micron copper is 0.98m 2 / g, and the average particle size is 3.01μm.
[0129] S45, weighing micron copper and nano copper with a particle size of 50 nm, wherein the mass ratio of micron copper to nano copper is 1: 1. Mixing the micron copper and nano copper and embedding the nano copper into the concave spots of the micron copper to obtain composite copper powder.
[0130] Specifically, micron copper and nano copper were premixed for 50 minutes to obtain a premix, and then zirconium beads with a diameter of 3 mm were added, and the mass ratio of zirconium beads to the premix was 3:1. Composite copper powder was obtained after ball milling for 20 hours.
[0131] Example 5 The preparation method of the composite copper powder in this embodiment comprises the following steps: S51, weighing a soluble copper salt and a pore-forming agent, dissolving them in a first alkaline solution, and mixing them evenly to obtain a first solution. The molar ratio of copper ions in the soluble copper salt to the pore-forming agent is 1:6.
[0132] Specifically, the soluble copper salt is copper sulfate. The pore-forming agent is ammonium sulfate and ethylenediamine. The first alkaline solution includes ammonia water, potassium hydroxide and pure water, and the total mass of ammonia water and potassium hydroxide accounts for 20%.
[0133] S52, weighing a reducing agent and a dispersing agent, and dissolving them in a second alkaline solution to obtain a second solution, wherein the molar ratio of the reducing agent to the copper ions in the soluble copper salt is 2:1.
[0134] The reducing agent is hydrazine hydrate. The dispersant is hexadecyltrimethylammonium bromide. The mass ratio of the dispersant to the copper particles is 0.05:1.
[0135] The second alkaline solution includes potassium hydroxide and pure water, and the mass proportion of potassium hydroxide is 10%.
[0136] S53, the first solution and the second solution are mixed rapidly under stirring, and reacted at 80° C. for 120 min. After the reaction is completed, the mixture is cooled to room temperature, and the solid and liquid are separated to obtain copper particles. The copper particles are in a plush state.
[0137] Specifically, the mixing time of the first solution and the second solution is 18 s.
[0138] S54, adding the copper particles into the solvent, mixing evenly, adding the coating agent, stirring for 30 minutes, separating the solid and the liquid, and vacuum drying to obtain micron copper.
[0139] The coating agent is imidazole, the solvent is pure water, and the mass ratio of the coating agent to the copper particles is 0.005:1.
[0140] In this embodiment, the specific surface area of micron copper is 2.33m 2 / g, and the average particle size is 1.1μm.
[0141] S55, weighing micron copper and nano copper with a particle size of 50 nm, the mass ratio of micron copper to nano copper being 3: 1. Mixing the micron copper and nano copper and embedding the nano copper into the pits of the micron copper to obtain composite copper powder.
[0142] Specifically, micron copper and nano copper were premixed for 40 minutes to obtain a premix, and then zirconium beads with a diameter of 6 mm were added, and the mass ratio of zirconium beads to the premix was 7:1. Composite copper powder was obtained after ball milling for 10 hours.
[0143] Example 6 The preparation method of the composite copper powder in this embodiment comprises the following steps: S61, weighing a soluble copper salt and a pore-forming agent, dissolving them in a first alkaline solution, and mixing them evenly to obtain a first solution. The molar ratio of copper ions in the soluble copper salt to the pore-forming agent is 1:6.
[0144] Specifically, the soluble copper salt is copper sulfate. The pore-forming agent is ammonium chloride and ammonium sulfate. The first alkaline solution includes sodium hydroxide and pure water, and the mass proportion of sodium hydroxide is 30%.
[0145] S62. Weigh a reducing agent and a dispersing agent, and dissolve them in a second alkaline solution to obtain a second solution, wherein the molar ratio of the reducing agent to the copper ions in the soluble copper salt is 8:1.
[0146] The reducing agent is hydrazine hydrate, the dispersing agent is gum arabic, and the mass ratio of the dispersing agent to the copper particles is 0.001:1.
[0147] The second alkaline solution includes sodium hydroxide and pure water, and the mass proportion of sodium hydroxide is 2%.
[0148] S63, the first solution and the second solution are mixed rapidly under stirring, and reacted at 80° C. for 15 minutes. After the reaction is completed, the mixture is cooled to room temperature, and the solid and liquid are separated to obtain copper particles. The copper particles are in a plush state.
[0149] Specifically, the mixing time of the first solution and the second solution is 45 s.
[0150] S64, adding copper particles to the solvent, mixing evenly, adding a coating agent, stirring for 30-60 minutes, separating the solid and liquid, and vacuum drying to obtain micron copper.
[0151] The coating agent is oleic acid, the solvent is anhydrous ethanol, and the ratio of the mass of the coating agent to the mass of the copper particles is 0.01:1.
[0152] In this embodiment, the specific surface area of micron copper is 2.89 m 2 / g, and the average particle size is 1.5μm.
[0153] S65, weighing micron copper and nano copper with a particle size of 30 nm, the mass ratio of micron copper to nano copper being 3: 1. Mixing the micron copper and nano copper and embedding the nano copper into the pits of the micron copper to obtain composite copper powder.
[0154] Specifically, micron copper and nano copper were premixed for 45 minutes to obtain a premix, and then zirconium beads with a diameter of 7 mm were added, and the mass ratio of zirconium beads to the premix was 7:1. Composite copper powder was obtained after ball milling for 10 hours.
[0155] Example 7 The preparation method of the composite copper powder in this embodiment comprises the following steps: S71, weighing a soluble copper salt and a pore-forming agent, dissolving them in a first alkaline solution, and mixing them evenly to obtain a first solution. The molar ratio of copper ions in the soluble copper salt to the pore-forming agent is 2:1.
[0156] Specifically, the soluble copper salt is copper acetate monohydrate. The pore-forming agent is ammonium sulfate. The first alkaline solution includes sodium hydroxide, glycerol and ethylene glycol, and the mass proportion of sodium hydroxide and glycerol is 5%.
[0157] S72. Weigh a reducing agent and a dispersing agent, and dissolve them in a second alkaline solution to obtain a second solution, wherein the molar ratio of the reducing agent to the copper ions in the soluble copper salt is 1:1.
[0158] The reducing agent is ascorbic acid, the dispersing agent is gelatin, and the mass ratio of the dispersing agent to the copper particles is 0.001:1.
[0159] The second alkaline solution includes sodium hydroxide, glycerol and ethylene glycol, and the mass proportion of sodium hydroxide and glycerol is 2%.
[0160] S73, the first solution and the second solution are mixed rapidly under stirring, and reacted at 130° C. for 130 minutes. After the reaction is completed, the mixture is cooled to room temperature, and the solid and liquid are separated to obtain copper particles. The copper particles are in a plush state.
[0161] Specifically, the mixing time of the first solution and the second solution is 25 s.
[0162] S74. Add the copper particles into the solvent, mix well, add the coating agent, stir for 35 minutes, separate the solid and liquid, and vacuum dry to obtain micron copper.
[0163] The coating agent is stearic acid, the solvent is anhydrous ethanol, and the mass ratio of the coating agent to the copper particles is 0.005:1.
[0164] In this embodiment, the specific surface area of micron copper is 2.7 m 2 / g, and the average particle size is 1.03μm.
[0165] S75, weighing micron copper and nano copper with a particle size of 30 nm, the mass ratio of micron copper to nano copper being 3: 1. Mixing the micron copper and nano copper and embedding the nano copper into the pits of the micron copper to obtain composite copper powder.
[0166] Specifically, micron copper and nano copper were premixed for 55 minutes to obtain a premix, and then zirconium beads with a diameter of 8 mm were added, and the mass ratio of zirconium beads to the premix was 7:1. Composite copper powder was obtained after ball milling for 10 hours.
[0167] Comparative Example 1 (Simple Mixture of Micron Copper and Nano Copper) The preparation method of the composite copper powder in this embodiment comprises the following steps: S81, weighing a soluble copper salt and a pore-forming agent, dissolving them in a first alkaline solution, and mixing them evenly to obtain a first solution. The molar ratio of copper ions in the soluble copper salt to the pore-forming agent is 1:6.
[0168] Specifically, the soluble copper salt is copper acetate monohydrate. The pore-forming agent is ammonium chloride. The first alkaline solution includes sodium hydroxide and pure water, and the mass proportion of sodium hydroxide is 30%.
[0169] S82. Weigh a reducing agent and a dispersing agent, and dissolve them in a second alkaline solution to obtain a second solution, wherein the molar ratio of the reducing agent to the copper ions in the soluble copper salt is 5:1.
[0170] The reducing agent is sodium ascorbate and glycerol. The dispersant is gelatin. The mass ratio of the dispersant to the copper particles is 0.001:1.
[0171] The second alkaline solution includes sodium hydroxide and pure water, wherein the mass proportion of the sodium hydroxide is 10%.
[0172] S83, the first solution and the second solution are mixed rapidly under stirring, and reacted at 80° C. for 60 minutes. After the reaction is completed, the mixture is cooled to room temperature, and the solid and liquid are separated to obtain copper particles. The copper particles are in a plush state.
[0173] Specifically, the mixing time of the first solution and the second solution is 50 s.
[0174] S84. Add the copper particles into the solvent, mix well, add the coating agent, stir for 40 minutes, separate the solid and liquid, and vacuum dry to obtain micron copper.
[0175] The coating agent is oleic acid, the solvent is ethanol, and the mass ratio of the coating agent to the copper particles is 0.005:1.
[0176] In this embodiment, the specific surface area of micron copper is 3.63m 2 / g, and the average particle size is 1.94μm.
[0177] S85. Weigh micron copper and nano copper with a particle size of 30 nm, with the mass ratio of micron copper to nano copper being 7:3. Simply mix the two to obtain composite copper powder.
[0178] Comparative Example 2 Copper powder with a particle size of 50 nm is commercially available.
[0179] The micron copper of Examples 1-7 was observed using a scanning electron microscope, and it was found that the micron copper of Examples 1-7 was velvety. This application only shows the scanning electron microscope spectrum of the micron copper in Example 2, such as Figure 3 As shown. Figure 3 It can be seen that the micron copper is velvety.
[0180] 16% by volume of an organic solvent was added to the copper powders of Examples 1 to 7 and Comparative Examples 1 to 2, respectively, and the mixture was mixed to obtain a solder paste having certain fluidity and viscosity.
[0181] An 80μm nano solder paste layer is prepared on a copper substrate by screen printing. Another copper plate is then placed on top of the solder paste. After preheating at 70°C for 20 minutes and keeping warm at 260°C under 10MPa pressure for 2 minutes, a semiconductor package can be obtained.
[0182] The semiconductor packages prepared in Examples 1-7 and Comparative Examples 1-2 were tested respectively, and the test data are shown in Table 1.
[0183] Table 1 Performance of semiconductor packages
[0184] It can be seen from Table 1 that the connection strength of the semiconductor packages of Examples 1 to 7 is better than that of Comparative Examples 1 and 2. The semiconductor packages of Examples 1 to 7 have no cracks on the surface, while the semiconductor packages corresponding to Comparative Examples 1 and 2 have obvious cracks.
[0185] Figure 4 , Figure 5 , Figure 6 The appearance pictures of the semiconductor packages corresponding to Example 2, Comparative Example 1 and Comparative Example 2 after sintering are shown respectively. It can be seen from the pictures that the semiconductor package corresponding to Example 2 has no obvious cracks, while the semiconductor packages corresponding to Comparative Example 1 and Comparative Example 2 have not only obvious cracks but also more cracks.
[0186] Although the present invention has been described with reference to several typical embodiments, it should be understood that the terms used are illustrative and exemplary, rather than restrictive. Since the present invention can be embodied in a variety of forms without departing from the spirit or essence of the invention, it should be understood that the above embodiments are not limited to any of the foregoing details, but should be interpreted broadly within the spirit and scope defined by the appended claims, so all changes and modifications falling within the scope of the claims or their equivalents should be covered by the appended claims.
Claims
1. A method for preparing a composite copper powder, characterized in that: The following steps are involved: Weighing a soluble copper salt and a pore-forming agent, dissolving them in a first alkaline solution, and mixing them evenly to obtain a first solution, wherein the molar ratio of copper ions in the soluble copper salt to the pore-forming agent is (12-1):6; the pore-forming agent is an ammonium salt; Weighing a reducing agent and a dispersing agent, and dissolving them in a second alkaline solution to obtain a second solution, wherein the molar ratio of the reducing agent to the copper ions in the soluble copper salt is (10-1):1; The first solution and the second solution are quickly mixed under stirring, and reacted at 80-160° C. for 15-120 minutes. After the reaction is completed, the mixture is cooled to room temperature, and solid-liquid separation is performed to obtain copper particles; the copper particles are in a plush state; The copper particles are added to the solvent, mixed evenly, and then the coating agent is added and stirred for 30-60 minutes, the solid-liquid separation is carried out, and the particles are vacuum dried, and then passed through a 80-800 mesh sieve to obtain particles with a diameter of 1-6 μm and a specific surface area of 0.2-8 m 2 / g of plush micron copper; The micron copper and nano copper with a particle size of 10-100 nm are weighed, the mass ratio of the micron copper to the nano copper is (1-81):9, the micron copper and the nano copper are mixed, and the nano copper is embedded in the pits of the micron copper to obtain a composite copper powder.
2. The method for preparing the composite copper powder according to claim 1, characterized in that: The size of the pits is ≤100 nm, and the particle size of the nano copper is not greater than the size of the pits; The mixing time of the first solution and the second solution is less than 3 min.
3. The method for preparing the composite copper powder according to claim 1, characterized in that: The step of mixing the micron copper and the nano copper and embedding the nano copper into the pits of the micron copper to obtain the composite copper powder comprises: The micron copper and the nano copper are premixed for 30-60 minutes to obtain a premix, and then ball milling beads with a diameter of 2-10 mm are added, the mass ratio of the ball milling beads to the premix is (3-20):1, and composite copper powder is obtained after ball milling for 4-20 hours.
4. The method for preparing the composite copper powder according to claim 3, characterized in that: The ball milling beads are ceramic beads; After ball milling, the powder is passed through a 80-800 mesh sieve to obtain a composite copper powder with a particle size of 1-10 μm.
5. The method for preparing the composite copper powder according to claim 1, characterized in that: The soluble copper salt includes at least one of copper sulfate, copper nitrate, copper chloride, copper acetate, copper citrate and hydrates thereof; The pore-forming agent includes at least one of ammonium chloride, ammonium bromide, ammonium sulfate, ammonium bicarbonate, ammonium carbonate, urea, ethylenediamine, triethanolamine, and triethylamine.
6. The method for preparing the composite copper powder according to claim 1, characterized in that: The first alkaline solution and the second alkaline solution both include an alkaline substance and a solvent, the alkaline substance includes at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, ethylenediamine, and ammonia water, and the solvent includes at least one of pure water, ethanol, ethylene glycol, glycerol, isopropanol, and polyethylene glycol; The alkaline substance accounts for 5-30% of the first alkaline solution, and the alkaline substance accounts for 2-20% of the second alkaline solution.
7. The method for preparing composite copper powder according to claim 1, characterized in that: The mass ratio of the dispersant to the copper particles is (0.001-0.05): 1; The dispersant includes at least one of gelatin, polyvinyl pyrrolidone, gum arabic, benzimidazole, 2-methylimidazole, 2-phenylimidazole, imidazole, and hexadecyltrimethylammonium bromide; The reducing agent includes at least one of sodium hypophosphite, sodium ascorbate, ascorbic acid, hydrazine hydrate, glucose, sodium borohydride and glycerol.
8. The method for preparing composite copper powder according to claim 1, characterized in that: The coating agent includes at least one of stearic acid, oleic acid, benzimidazole, 2-methylimidazole, 2-phenylimidazole and imidazole, and the solvent includes at least one of anhydrous ethanol, ethylene glycol, pure water, acetone, ether, glycerol and acetone; the mass ratio of the coating agent to the copper particles is (0.005-0.1):
1.
9. A composite copper powder, characterized in that: The composite copper powder is prepared by the preparation method described in any one of claims 1 to 8.
10. A method for preparing a semiconductor package, characterized in that: The following steps are involved: Using the composite copper powder prepared by the preparation method according to any one of claims 1 to 8 as a raw material to prepare and obtain a solder paste; The two substrates are welded with the solder paste to obtain a semiconductor package.
11. A semiconductor package, characterized in that: The invention comprises two substrates and a solder paste layer located between the two substrates, wherein the solder paste layer is prepared using the composite copper powder prepared by the preparation method according to any one of claims 1 to 8 as a raw material.
Citation Information
Patent Citations
Multi-hole micrometer copper ball and preparation method thereof
CN105458295A
Nanometer copper paste for chip pressureless sintering interconnection and preparation method and application thereof
CN111975011A
Preparation method of composite soldering paste
CN113523649A
Copper powder with particle size in three-peak distribution from nanometer to micrometer and one-time synthesis method and application thereof
CN114054746A
Copper soldering paste and preparation method and application thereof
CN114799613A